2021
DOI: 10.46743/2160-3715/2021.4728
|View full text |Cite
|
Sign up to set email alerts
|

A Journey of Hidden Outburst of Anger Shackling a Person with Schizophrenia: The Indonesian Context

Abstract: Shackling a person with schizophrenia violates human rights. This process is often carried out when the person has committed acts of violence and hostility. In this study, we focus on considering the shackling of a person with schizophrenia in Indonesia’s context. We used grounded theory (GT; Charmaz, 2011) with 23 participants located in the East Java Province, Indonesia. The participants consisted of people with schizophrenia who were shackled by their ankles, families treating people with schizophrenia, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Research shows that ACE therapy with active/effective contact with the environmental activities supports patients to get to know the environment. 25 A study of 104 patients with schizophrenia showed that the patients used more negative than positive strategies (mean T-score for negative strategies was 59.04±11.24 vs 49.5±11.8 for positive approaches). Negative strategies include escape tendency, perseveration, resignation, and self-accusation.…”
Section: Coping Mechanismmentioning
confidence: 99%
“…Research shows that ACE therapy with active/effective contact with the environmental activities supports patients to get to know the environment. 25 A study of 104 patients with schizophrenia showed that the patients used more negative than positive strategies (mean T-score for negative strategies was 59.04±11.24 vs 49.5±11.8 for positive approaches). Negative strategies include escape tendency, perseveration, resignation, and self-accusation.…”
Section: Coping Mechanismmentioning
confidence: 99%
“…Schizophrenia is a mental disorder with symptoms such as thinking, feeling, and behaving (Windarwati et al, 2021). People with schizophrenia have lost contact with reality, causing difficulties for the individual and those around them (Hidayah et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…East Java Province has been particularly hard hit, with the highest rate of mental health problems in Indonesia, including severe mental disease such as schizophrenia (East Java Province Riskesdas Team, 2019). The stigma associated with mental illness (Widodo et al, 2019;Windarwati et al, 2021;Baklien et al, 2022), compounded by the harsh conditions of institutionalization and shackling, leads to many individuals with mental illness being subjected to these circumstances. Such practices are often attributed to familial shame or fear of their mentally ill family members' violent outbursts.…”
Section: Introductionmentioning
confidence: 99%